STUDI ESTIMASI BIAYA PEMOTONGAN PELAT SECARA MANUAL BERDASARKAN WAKTU PROSES DAN KONSUMSI GAS POTONG PADA GALANGAN KAPAL - Bagus Kusuma Aditya; Tri Agung Kristiyono (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
One of the dominant activities in the production process in shipyards is plate cutting. So that in this process, the cost of the cutting process will also have a large enough share. In the shipyard, manual cutting is still often encountered because the position and location of the plate cutting varies, although technologically there are automatic cutting machines which tend to be tied to the cutting location. In the Oxy-Lpg plate cutting study that has been carried out, the regression results are obtained, with the time equation Y = 33.826X – 0.9026, the Lpg consumption equation Y= 0.057 + 0.017X and the Oxygen consumption equation Y= -0.415 + 0.127X. based on the existing equation, the cost analysis of the cutting process obtained the cost of cutting the 6 mm plate IDR. 13,400 rupiah, the 8 mm plate IDR. 20,000 rupiah, 10 mm plate IDR 26,700 rupiah, 12 mm plate IDR 33,325 rupiah and 14 mm plate IDR 40,000 rupiah with a cutting length 100 cm